Comportamiento Epizootiológico de Parásitos Gastrointestinales en Caninos Domésticos (canis familiaris) en el Barrio “Santa Rosa de Pichul” del Canton Latacunga. - Ramos del Castillo, Leonardo Andrés (2018)
Nowadays, infections by gastrointestinal parasites are very common and frequent in dogs, generating various alterations to their health; such as diarrhea, anorexia, appetite reduction, interference in the absorption and conversion of nutrients, and intestinal obstructions which can lead to death. In addition, they cause a zoonosis problem for humans. The general objective of this research work was to determine the epizootiological behavior of gastrointestinal parasites in domestic dogs (canis familiaris) through the coprological analysis to structure prevention measures against zoonotic parasitic diseases. The research was carried out by obtaining 150 stool samples from the same number of dogs from the "Santa Rosa de Pichul" neighborhood. The laboratory analysis was carried out using the flotation with sucrose solution technique and microscope observation for the gastrointestinal parasites count to verify the number and percentage of these, and therefore, set the incidence of the parasitic load that generates a public health problem. We obtained a high rate of parasitism with a prevalence of 88 positives from 150 dogs with a 58.67%. In dogs from 0 to 12 months, there was n=44 representing the 29.33%; from 1 to 5 years old, n=34 (22.67%); > to 5 years old, n=10 (6.67%). Males with n=51 (34%) indicate a higher percentage than females; n=37 (24.67%). In dogs of small breeds, n=23 (15.33%); medium breeds, n=47 (31.33%); and large breeds, n=18 (12%) of parasitic load. Ancylostoma caninum (52,27%), followed by Toxocara canis (26,14%), Uncinaria stenocephala (14,77%), and Dipylidium caninum (6,82%) were found. From 0-12 months (Ancylostoma caninum 23,86%, Toxocara canis 13,64%, Uncinaria stenocephala 9,09%, Dipylidium Caninum 3,41%)., from 1-5 years old (Ancylostoma caninum 21,59%, Toxocara canis 10,23%, Uncinaria stenocephala 3,41%, Dipylidium Caninum 3,41%) and dogs > to 5 years old (Ancylostoma caninum 6,82 %, Toxocara canis 2,27 %, Uncinaria stenocephala 2,27 %, Dipylidium Caninum 0%). Males (Ancylostoma caninum 32,95%, Toxocara canis 12,50%, Uncinaria stenocephala 5,68%, Dipylidium Caninum 6,82%), females (Ancylostoma caninum 19,32%, Toxocara canis 13,64%, Uncinaria stenocephala 9,09%, Dipylidium Caninum 0,00%). Small breeds (Ancylostoma caninum 15,91%, Toxocara canis 5,68%, Uncinaria stenocephala 6,82%, Dipylidium Caninum 2,27%), medium breeds (Ancylostoma caninum 26,14%, Toxocara canis 14,77%, Uncinaria stenocephala 4,55%, Dipylidium Caninum 3,41%), and finally, large breeds (Ancylostoma caninum 10,23%, Toxocara canis 5,68%, Uncinaria stenocephala 3,41%, Dipylidium Caninum 1,14%). According to the results, it is concluded that the dogs of medium breeds had a higher frequency of parasitism presence (48, 86%).The age that showed incidence was from 0-12 months (50%); there was a higher prevalence in males (57,95%). Finally, parasitism in the dogs evaluated is 58.67%, being Ancylostoma caninum (52,27%) the most frequent.